Attenuation of STZ‐induced diabetic nephropathy by Cucurbita pepo L. seed extract characterized by GCMS. Issue 6 (14th September 2017) - Kaur, Navpreet; Kishore, Lalit; Singh, Randhir
Abstract: The present study was aimed to evaluate the potential of petroleum ether and hydro‐alcoholic extract of Cucurbita pepo (CPE and CHE) in STZ‐induced diabetic nephropathy. GC‐MS analysis of CPE revealed the presence of different fatty acids, heterocyclic compounds, and so on. Diabetes was induced by intraperitoneal administration of STZ (65 mg/kg) for the development of diabetic nephropathy. After 30 days of STZ‐administration, 100, 200, and 400 mg/kg of CPE and CHE were administered for 45 days. CPE and CHE significantly increased body weight, lowered blood glucose levels, and ameliorated kidney hypertrophy index in the STZ‐diabetic rats. The extract also decreased the levels of creatinine, blood urea nitrogen, total cholesterol, triglycerides, AGEs and albumin in urine, respectively. The results indicated that via amelioration oxidative stress and formation of AGEs, C. pepo produced significant nephroprotective effect in STZ‐ induced diabetic nephropathy in rats. Practical applications: DN is a syndrome mainly characterized as increase in excretion of urine albumin, urea, uric acid, and creatinine; glomerular lesions and reduce glomerular filtration rate (GFR) in diabetics. Fruit and seeds of Cucurbita pepo have significant hypoglycemic and antioxidant activity. C. pepo possesses antioxidant, antihyperglycemic, antihyperlipidemic, and antiglycation activity and thus, exhibits a protective action in STZ‐induced diabetic nephropathy. Moreover, further work is necessary to elucidate in detail the mechanism of action of C. pepo at the cellular and molecular levels.